The Implementation of Critical Thinking in Bahtsul Masail Activities at Fathul Ulum Islamic Boarding School Jombang - Shinta Ananda Putri; Rofi'ah, Siti (Journal Of Islamic Education And Pesantren, 2023)
Critical thinking is a cognitive process involving the ability to analyze, evaluate, and question information before accepting it as truth, enabling individuals to formulate reasoned opinions and make sound decisions based on credible sources. In the pesantren context, one strategic effort to cultivate critical thinking among santri is through participation in Lajnah Bahtsul Masail activities, commonly known as Bahtsul Masail. This study aims to examine: (1) the process of implementing critical thinking in Bahtsul Masail activities, and (2) the supporting and inhibiting factors influencing its implementation. The research employs a qualitative approach with a case study design. Data were collected through interviews, observation, and documentation involving the pesantren caretaker, LBM administrators, and santri. Data analysis was conducted using source triangulation techniques to ensure validity and credibility. The findings reveal that the implementation of critical thinking in Bahtsul Masail requires santri to identify problems, analyze classical Islamic texts, construct arguments, and formulate solutions to contemporary issues. Supporting factors include adequate facilities, motivational reinforcement regarding the importance of Bahtsul Masail, students’ enthusiasm, routine classroom deliberations, and structured LBM management. Inhibiting factors consist of limited student motivation, insufficient literacy in classical texts and Arabic grammar, and lack of coordination among LBM administrators, which may reduce the effectiveness of the program.